Crematie van de gevallen leden van het MLL-Front. Aula aan de PC Hooftstraat 181-183. Serie van 3 foto's
Crematie van de gevallen leden van het MLL-Front. Aula aan de PC Hooftstraat 181-183. Serie van 3 foto's.